Determination of Logistics Risk of Palm Cooking Oil Using Fuzzy Delphi Method and Fuzzy Analytical Hierarchy Process - Ahmad Munawar, Niknik; Mahaputra, M. Rizky (Siber Nusantara Research & Yayasan Sinergi Inovasi Bersama (SIBER), 2023)
Determination of risk sources and risk indicators is carried out by conducting literature studies and expert assessments. The results of the expert assessment are processed using the Delphi fuzzy and AHP fuzzy methods. The Delphi fuzzy method is used to make decisions regarding risk sources and risk indicators based on expert opinion. The AHP fuzzy method is used to determine the weight and priority order of risk sources and risk indicators for palm cooking oil logistics. The risk sources obtained based on the study of the literature are as many as 10 risk sources which are then selected 8 risks that are approved by experts. While the risk indicators obtained based on the study of the literature are as many as 34 indicators, then as many as 23 indicators are considered important by experts. Based on the risk weight assessment, the order of risk with the highest weight is supply risk with a weight of 0.2803, partnership risk with a weight of 0.1619, production risk with a weight of 0.1576, storage risk with a weight of 0.1262, technology risk with weight of 0.93, transportation risk with a weight of 0.0811, infrastructure risk with a weight of 0.0603 and market risk with a weight of 0.0395.